Kinerja Pegawai Dalam Memberikan Pelayanan Publik Pada Kantor Kecamatan Pineleng Kabupaten Minahasa - Lintjewas, Debby D Y; Mamentu, Michael; Kawung, Evelin (JURNAL ILMIAH SOCIETY, 2016)
Subdistrict Pineleng entrance and exit for the flow of goods, people and traffic will be heading to Manado and Minahasa district to the capital. As the District that is located directly adjacent to the city of Manado where it is known as the capital of North Sulawesi province, thus requiring apparatus that has a high performance in providing public services. With high performance and good public services provided will be maximized. Therefore, the problem in this research is "Why does the performance of employees in providing public services in the District Office Pineleng Minahasa not running optimally?". This study aims to find answers related to the academic performance of Employees in providing public services in the District Office Pineleng Minahasa regency. This study used a qualitative approach with descriptive analysis method. The results using the indicators of employee performance 1) Quality of work; 2) Pomptness; 3) Initiative; 4) Capability; 5) Communication, it is known why the employee's performance is not maximized because: 1) Lack of employees at the District Office Pineleng; 2) An employee in performing the tasks of public service, is still a lack of discipline; 3) Human resources (HR) at the Head Office Pineleng have low competence. 4) Supporting facilities and infrastructure for public services available memperancar still lacking